Apically Dominant Mechanism for Improving Catalytic Activities of N‐Doped Carbon Nanotube Arrays in Rechargeable Zinc–Air Battery. Issue 20 (14th April 2018) - Niu, Wenhan; Pakhira, Srimanta; Marcus, Kyle; Li, Zhao; Mendoza‐Cortes, Jose L.; Yang, Yang
Abstract: The oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) in zinc–air batteries (ZABs) require highly efficient, cost‐effective, and stable electrocatalysts as alternatives to high cost and low poison resistant platinum group metals (PGM) catalysts. Although nitrogen‐doped carbon nanotube (NCNT) arrays are now capable of catalyzing ORR efficiently, their hydrophobic surface and base‐growth mode are found to limit the catalytic performance in the practical ZABs. Here, the concept of an apically dominant mechanism in improving the catalytic performance of NCNT by precisely encapsulating CoNi nanoparticles (NPs) within the apical domain of NCNT on the Ni foam (denoted as CoNi@NCNT/NF) is demonstrated. The CoNi@NCNT/NF exhibits a more excellent catalytic performance toward both ORR and OER than that of traditional NCNT derived from the base‐growth method. The ZAB coin cell using CoNi@NCNT/NF as an air electrode shows a peak power density of 127 mW cm −2 with an energy density of 845 Wh kgZn −1 and rechargeability over 90 h, which outperforms the performance of PGM catalysts. Density functional theory calculations reveal that the ORR catalytic performance of the CoNi@NCNT/NF is mainly attributed to the synergetic contributions from NCNT and the apical active sites on NCNT near to CoNi NPs. Abstract : A concept of apical dominance in the preparation of nitrogen‐doped carbon nanotubes is demonstrated in this work. Such carbon nanostructures can efficiently catalyze oxygen electrochemical reactions in Zn–air batteries, which deliver good cycling performance over 90 h and a power density of 127 mW cm −2 in practical coin cells.